PECULIARITIES OF THE KYRGYZ GOD-WORSHIPING TRADITION (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
Every parent thinks and cares about the future and good life of their children. The Kyrgyz consider the marriage of their children to be the parents’ duty. This wedding tradition begins with the engagement and sending a matchmaker to the girl’s parents. The article discusses the Kyrgyz tradition of wrestling and its features. The wedding ceremony of the Kyrgyz is similar to the wedding ceremony of the peoples living in Central Asia. Engagement is an agreement and promise of marriage between parents before marriage. Engagement is one of the main parts of the wedding ceremony. In the Kyrgyz language, there are types of engagement: bel kuda, besik kuda, kaichy kuda. The engagement began with a visit by the boy’s parents or a matchmaker sent by them to the girl’s parents or close relatives. The main task of the intermediary was to obtain the consent of the bride’s father to the upcoming marriage.
Keywords: wedding ceremony, engagement, matchmaker, back to God, beshik kuda, kaychy kuda, rituals, customs and traditions.